Anti-tobacco mosaic virus (TMV) activity of chemical constituents from the seeds of Sophora tonkinensis. Issue 7 (28th June 2021) - Hu, Zhan-Xing; Zou, Ji-Bin; An, Qiao; Yi, Ping; Yuan, Chun-Mao; Gu, Wei; Huang, Lie-Jun; Lou, Hua-Yong; Zhao, Li-Hua; Hao, Xiao-Jiang
Abstract: Two new compounds, including one new arylbenzofuran (1 ) and one new pterocarpanoid (2 ), along with nine known ones, were isolated from the seeds of Sophora tonkinensis. The structures of the new compounds were elucidated based on a comprehensive spectroscopic data analysis. Compounds 2 and 3 exhibited good anti-tobacco mosaic virus (TMV) activities with the protective inhibition rate of 69.62% and 68.72% respectively, at concentration of 100 μ g/ml. Graphical Abstract: UF0001